(untitled) (Journal of Philosophy, Culture and Political Science, 2026)
This study examines the primary motivations of tourists visiting Turkestan, focusing on the influence of its UNESCO World Heritage Site (WHS) status, specifically the Mausoleum of Khoja Ahmed Yasawi, on visitor decisions. Employing a survey of 137 respondents from diverse age and gender groups, the research explores factors such as historical and cultural appeal, leisure, spiritual experiences, and prior knowledge. The findings highlight that the UNESCO WHS designation significantly enhances Turkestan’s prestige, with the majority of visitors citing cultural and historical exploration as key motivators. However, a substantial portion of respondents remain unaware of the site’s UNESCO status, indicating a need for improved promotional strategies. The study also reveals that prior knowledge of Turkestan’s rich history and culture positively influences visitors’ sense of authenticity and connection. Recommendations for improvement include enhanced signage, infrastructure upgrades, and expanded cultural programs to address logistical challenges and deepen engagement. Additionally, opportunities exist to diversify tourism offerings, such as adventure and luxury experiences, to attract broader audiences. This research underscores the dual role of UNESCO WHS designation as a tool for heritage preservation and sustainable tourism development. By addressing identified gaps, Turkestan can further position itself as a leading cultural and spiritual tourism destination, contributing to regional and global tourism growth. Keywords: Heritage tourism, UNESCO World Heritage Site, tourist motivation, cultural tourism, Turkestan, Khoja Ahmed Yasawi Mausoleum